Mengungkap kompleksitas kausal: Tinjauan sistematis dan kritik terhadap pendekatan linear dalam penelitian prestasi matematika - Filiestianto, Gerry; Kusumah, Yaya Sukjaya (IKIP Siliwangi, 2025)
However, the current body of research is dominated by linear approaches that possess a limited capacity to uncover how various factors interact in complex ways. This study aims to address this need through a Systematic Literature Review. The methodology followed the PRISMA 2020 guidelines, involving a systematic search of the Scopus and Google Scholar databases, which resulted in 40 core studies for final synthesis. The findings reveal that student-internal psychological and affective variables are the most dominant focus of current research. Methodologically, the field heavily relies on quantitative approaches, particularly Structural Equation Modeling (SEM). The most significant finding is a consistent research gap regarding the lack of understanding of the complex, configurational interactions among multiple factors, as most studies employ linear-based analyses. This review concludes that there is an urgent need for research using configurational approaches, such as fs/QCA, to uncover the multiple causal pathways to mathematics achievement. The primary contribution of this study is the presentation of a critical framework that offers a configurational perspective as an alternative to linear models for a more holistic understanding of student success.